Oestrogen and progesterone receptor assessment in core biopsy specimens of breast carcinoma. Issue 1 (January 1997) - Zidan, A; Christie Brown, J S; Peston, D; Shousha, S
Abstract : AIMS: To assess the suitability of core biopsy specimens for the immunohistological assessment of oestrogen and progesterone receptors in breast carcinoma. METHODS: Thirty consecutive cases of clinically palpable breast carcinoma, from which both core and excision biopsy specimens were available, were examined. Routinely processed paraffin wax sections were stained using the specific monoclonal antibodies 1D5 (Dako) for oestrogen receptor and NCL-PGR (Novocastra) for progesterone receptor, after an antigen retrieval step using a pressure cooker. Staining results were assessed using the H score system with the results being expressed as negative, weakly positive, moderately positive or strongly positive. RESULTS: Twenty six biopsy specimens contained enough tumour tissue for assessment. Absolute agreement between scoring categories was seen in 19 (73%) cases for oestrogen receptors. However, when all positive categories were added together, agreement between core and excision biopsy specimens increased to 93% (24 cases). Disagreement was seen only in two cases which stained positive in the core biopsy specimens and negative in the excision biopsy specimens. For progesterone receptors, the absolute agreement between all scoring categories was seen only in 11 (42%) cases. When all positive categories were considered together, agreement increased to 69% (18 cases). Five cases were progesterone receptor positive in core but not in excisional biopsy specimens, while three cases were negative in core but positive in excisional biopsy specimens. CONCLUSIONS: The results suggest that core biopsy specimens can be reliably used for oestrogen receptor assessment, but are less reliable for progesterone receptor assessment, probably because of a greater heterogeneity of progesterone receptor staining.